Liberal feminism, diversity and education - Penny Enslin (Theory and Research in Education 1(1) 2003, 2003)
Liberal feminism, like liberal political theory in general, is sometimes criticized for overemphasizing equality and the promotion of autonomy at the expense of valuing diversity. Some might thus see an approach to difference in education that is based on liberal feminism as a threat to cultural diversity. This article argues that although cultural diversity has some benefits, liberal feminism should not be deterred from promoting autonomy and equality for women by encouraging the alteration of practices that harm their interests. Siding with Susan Moller Okin's liberal feminism in Is Multiculturalism Bad for Women? the contrast between comprehensive and political liberalism in recent work by Okin and by Martha Nussbaum is explored. It is claimed that a liberal feminist approach to the education of women and girls would necessarily be a form of comprehensive liberalism.